2012
DOI: 10.4103/0970-9290.102234
|View full text |Cite
|
Sign up to set email alerts
|

Marginal microleakage of resin-modified glass-ionomer and composite resin restorations: Effect of using etch-and-rinse and self-etch adhesives

Abstract: Use of two-step self-etch adhesive, prior to restoring cervical cavities with RMGIC, seems to be more efficacious than the conventional cavity conditioner in decreasing marginal microleakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 15 publications
1
22
0
3
Order By: Relevance
“…Theoretical and experimental considerations of the wear and mechanical properties of nanofilled and nanohybrid composites, as compared with materials containing fillers in the micrometer range, have indicated the improved performance of the nanofilled and nanohybrid composites. 13 Recently, Palaniappan and others 43 tested the null hypothesis that there are no differences between the clinical-wear performances of nanofilled, microfilled, and conventional hybrids placed in Class I and Class II cavities. The findings of the five-year clinical trial revealed that operators and preparation type can affect restoration wear magnitude but do not contribute to increased functional risk of fracture or harmful effects on pulp and periodontal biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Theoretical and experimental considerations of the wear and mechanical properties of nanofilled and nanohybrid composites, as compared with materials containing fillers in the micrometer range, have indicated the improved performance of the nanofilled and nanohybrid composites. 13 Recently, Palaniappan and others 43 tested the null hypothesis that there are no differences between the clinical-wear performances of nanofilled, microfilled, and conventional hybrids placed in Class I and Class II cavities. The findings of the five-year clinical trial revealed that operators and preparation type can affect restoration wear magnitude but do not contribute to increased functional risk of fracture or harmful effects on pulp and periodontal biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported 43 that the analysis of variance of bond strength data becomes more consistent when the specimens lost prematurely are considered for statistical analysis and that their omission can provide a significant overestimation of the results. Many studies in the literature do not consider premature failures; consequently, those findings might not accurately reflect the bonding performance, 44,45 leading to false interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations